Preconditions for the Formation of the Institute of Lease of State-owned Land and its Evolution - Pikūnas, Ainius; Rečiūnaitė, Rytė (Vilnius University Open Series, 2024)
The research work analyses the preconditions for the formation of the institute of lease of state-owned land, discussing the historical context of the emergence of such regulation, reviewing the development of legislation of this institute, the case law interpreting it and the jurisprudence of the Constitutional Court. The formation of the institute of lease of state-owned land was mainly influenced by the prohibition of ownership of land by legal persons in the original wording of Article 47 of the Constitution, as well as by the peculiarities of the restitution and privatisation processes, which prevented the formation of private land masses, and became a prerequisite for the separation of the property complexes (i.e. the ownership of a land plot and the buildings on it).The authors of the paper, having studied the development of the regulation of state-owned land lease from 1992 to 2022, described state-owned land lease as an independent civil law institute, which combines the public law regulation method and strict principles of state property management with the general principles of civil relations (equality of the parties, inviolability of property, proportionality), and seeks to ensure the correct balance between the interests of society and the rights of the owner. The specific regulation of state-owned land lease in the legal system of the Republic of Lithuania and the wide spread of state-owned land lease relations have prevented the real implementation of the Roman law principle superficies solo cedit in Lithuanian property law: although this principle is established in the Civil Code, its exceptions are applied very often, thus preventing the actual dominance of the principle in the legal system of Lithuania.